STRATEGIC MARKETING FOR F&B BUSINESS - Goenawan, Theodorus
This strategic marketing analysis focuses on Siomay Bandung Wibisana in the Food and Beverage (FnB) industry. It explores the implementation of a comprehensive marketing strategy integrating Segmentation, Targeting, and Positioning (STP), SWOT analysis, and the classic 4Ps (Product, Price, Place, Promotion). The aim is to differentiate Siomay Bandung Wibisana within the competitive F&B landscape, align marketing initiatives with business objectives, and foster sustained growth. This study emphasizes the need for an adaptable, responsive marketing approach tailored to market shifts to ensure enduring success in the dynamic FnB industry. The research methods encompass a diverse range of approaches. Firstly, surveying and conducting interviews with both existing patrons and prospective customers to extract firsthand insights forms a pivotal part. Secondary data analysis plays a crucial role, involving a meticulous examination of historical sales figures, customer feedback, and competitive intelligence sourced externally. Additionally, user testing through focus groups or direct user assessments serves to gauge and understand user experiences effectively. Lastly, delving into competitive case studies entails comprehensive research into the strategies and achievements of competitors operating within the same industry, providing a broader perspective for informed decisions and strategy formulation. Siomay Bandung Wibisana's success hinges on a comprehensive strategy integrating STP and SWOT analyses with the 4Ps. This approach sets it apart in the competitive F&B scene, aligning marketing with business goals for sustained growth. In summary, a well-rounded, adaptable strategy tailored to market shifts positions the brand for lasting success in the dynamic F&B landscape.